Biosignal and medical image processing - Semmlow, John L.; Griffel, Benjamin
"This third edition of a bestseller offers comprehensive coverage of the major approaches in biomedical signal and image processing. It provides a complete set of signal processing tools, including diagnostic decision-making tools, and classification methods. Thoroughly revised and updated, it supplies important new material on nonlinear methods for describing and classifying signals, including entropy-based methods and scaling methods. This edition covers data "cleaning" methods commonly used in such areas as heart rate variability studies, along with actual examples. It also includes new end-of-chapter problems"--Provided by publisher.
Keywords: Signal Processing, Computer-Assisted; Biosensing Techniques; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted